Sosialisasi Dan Pendampingan Hukum Pendirian Koperasi Desa Merah Putih Di Kecamatan Mojogedang Dan Kecamatan Karanganyar Kabupaten Karanganyar - Sukarno, Karmila Sari; Nurviana, Reky; Buana, Nimas; Evi, Safira (CV. Kurnia Grup, 2025)
The Merah Putih Village Cooperative Program is a government initiative to strengthen the rural economy through the establishment of cooperatives in each village/sub-district. This study aims to analyze the level of public understanding of the legal aspects of cooperative establishment and formulate effective socialization and mentoring strategies in Mojogedang and Karanganyar Districts, Karanganyar Regency. The method used is community service through direct socialization and two-way discussions with the community on June 2-3, 2025. The results of the study show that the public's understanding of the legal aspects of the establishment of cooperatives is still low, where most residents only understand cooperatives as a simple savings and loan container without mastering technical aspects such as legal requirements, deeds of establishment, and legalization of legal entities. The main obstacles identified include limited legal literacy, administrative barriers, minimal human resource capacity, socio-economic constraints, and lack of mentoring. To overcome these problems, a community-based socialization strategy, simplification of legal materials, direct assistance by experts, cooperative management training, and continuous monitoring and evaluation are needed. The implementation of this socialization and mentoring program is expected to increase community understanding and support the formation of the Merah Putih Village Cooperative which is not only legally legal but also sustainable in encouraging the village economy.